Teaching Children with Albinism in Nigerian Regular Classrooms: An Examination of the Contextual Factors - Kingsley Chinaza Nwosu; Gabriel Chidi Unachukwu; Victor Chekume Nwasor; Anthony Obinna Ezennaka (Centre for Behaviour and Wellness Advocacy, 2019)
The visual and dermatological conditions of children with albinism (CWA) demand that special attention is given to them to enable them to cope with their studies and daily living. In spite of the fact that they have equal intellectual abilities with their counterparts, a good number of them perform poorly in school and are likely to drop out of school. This study examined the belief/knowledge of teachers and educational practices adopted in Nigerian public secondary schools for CWA. One hundred and six (106) teachers from 12 secondary schools in Anambra State that teach CWA participated in the study. Major findings showed that regular classrooms were not albinism-friendly with regards to the provision of facilities; a good number of the respondents had faulty beliefs and poor knowledge about albinism, and teachers reported that they adopted albinism-friendly instructional and assessment practices. Teachers encountered a number of challenges in teaching CWA such as inadequate instructional facilities, difficulty getting their classmates to accept them in class and inadequate time to attend to them. There was no significant difference in the hypotheses tested except in the school location and instructional practices of teachers. Based on these, recommendations and limitations of the study were highlighted.